2019
DOI: 10.3174/ajnr.a5944
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Brain Metabolites in Patients with Epilepsy with Impaired Consciousness: A Case-Control Study of Interictal Multivoxel 1H-MRS Findings

Abstract: BACKGROUND AND PURPOSE:Previous studies have shown perfusion abnormalities in the thalamus and upper brain stem in patients with epilepsy with impaired consciousness. We hypothesized that these areas associated with consciousness will also show metabolic abnormalities. However, metabolic abnormalities in those areas correlated with consciousness has not been characterized with multiplevoxel 1 H-MRS. In this study, we investigated the metabolic alterations in these brain regions and assessed the correlation bet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 47 publications
(60 reference statements)
0
14
0
Order By: Relevance
“…Bilateral hypermetabolism was seen in the brainstem, corpus callosum, and cingulate gyrus. Previous work supports the important role that the thalamus and upper brainstem play in attention, arousal, and maintaining consciousness (Blumenfeld, 2012;Calabrò et al, 2015;Koch et al, 2016;Tan et al, 2019). The thalamus is also a principal component of the limbic system and the ascending reticular activating system, which has distinct connections with the cingulate gyrus, reticular formation, and cerebral cortex (Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…Bilateral hypermetabolism was seen in the brainstem, corpus callosum, and cingulate gyrus. Previous work supports the important role that the thalamus and upper brainstem play in attention, arousal, and maintaining consciousness (Blumenfeld, 2012;Calabrò et al, 2015;Koch et al, 2016;Tan et al, 2019). The thalamus is also a principal component of the limbic system and the ascending reticular activating system, which has distinct connections with the cingulate gyrus, reticular formation, and cerebral cortex (Feng et al, 2017).…”
Section: Discussionmentioning
confidence: 71%
“…Regardless of MRI-positive and negative, cortical and subcortical brain regions related to TLE-IAS were found. A previous study based on MRI spectroscopy also found that metabolic changes in the brainstem and thalamus were observed in patients with epilepsy with impaired consciousness (Tan et al, 2019). Therefore, it is still necessary to further study the difference between MRI and PET in TLE-IAS patients.…”
Section: Discussionmentioning
confidence: 97%
“…The precuneus is crucial for maintaining consciousness in humans 23,24 . It forms part of the default mode network (DMN), which together with the brain stem and thalamus make up the consciousness system 25‐27 . Disturbed consciousness is a predominant clinical sign in SHE, and DMN‐related impairments in awareness have been observed in various types of epilepsy 28‐30 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the practicability of MRS in detecting epileptogenic inflammation is mainly limited by the intensity and power of the magnetic field, which affects the accurate quantification of different neurotransmitters [ 81 ]. It has been reported that 1 H-MRS is applied to detect epilepsy ranging from TLE [ 82 ] to idiopathic generalized epilepsy while it seems to be of little value for monitoring insular epilepsy [ 83 ].…”
Section: Brain Imaging Markersmentioning
confidence: 99%